AtoSC two-component system is involved in cPHB biosynthesis through fatty acid metabolism in E. coli - Theodorou, Evaggelos C; Theodorou, Marina C; Kyriakidis, Dimitrios A (Biochimica et biophysica acta, 2011)
BACKGROUND: We have shown previously that AtoSC two-component system regulates the biosynthesis of E. coli cPHB [complexed poly-(R)-3-hydroxybutyrate]. METHODS: The AtoSC involvement on fatty acids metabolism, towards cPHB synthesis, was studied using cPHB determination, gene expression, and fatty acid metabolic pathways inhibitors. RESULTS: Deletion of the atoDAEB operon from the E. coli genome resulted in a consistent reduction of cPHB accumulation. When in ΔatoDAEB cells, the atoDAEB operon and the AtoSC system were introduced extrachromosomally, a significant enhancement of cPHB levels was observed. Moreover, the introduction of a plasmid with atoSC genes regulated positively cPHB biosynthesis. A lesser cPHB enhancement was triggered when plasmids carrying either atoS or atoC were introduced. The intracellular distribution of cPHB was regulated by AtoSC or AtoC according to the inducer (acetoacetate or spermidine). Blockage of β-oxidation by acrylic acid reduced cPHB levels, suggesting the involvement of this pathway in cPHB synthesis; however, the overproduction of AtoSC or its constituents separately resulted in cPHB enhancement. Inhibition of fatty acid biosynthesis by cerulenin resulted to a major cPHB reduction, indicating the contribution of this pathway in cPHB production. Inhibition of both β-oxidation and fatty acid biosynthesis reduced dramatically cPHB, suggesting the contribution of both pathways in cPHB biosynthesis. CONCLUSIONS: Short fatty acid catabolism (atoDAEB operon) and fatty acids metabolic pathways participate in cPHB synthesis through the involvement of AtoSC system. GENERAL SIGNIFICANCE: The involvement of the AtoSC system in the fatty acids metabolic pathways interplay towards cPHB biosynthesis provides additional perceptions of AtoSC role on E. coli regulatory biochemical processes.